2016
DOI: 10.1523/jneurosci.3285-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Embedding a Panoramic Representation of Infrared Light in the Adult Rat Somatosensory Cortex through a Sensory Neuroprosthesis

Abstract: Can the adult brain assimilate a novel, topographically organized, sensory modality into its perceptual repertoire? To test this, we implemented a microstimulation-based neuroprosthesis that rats used to discriminate among infrared (IR) light sources. This system continuously relayed information from four IR sensors that were distributed to provide a panoramic view of IR sources, into primary somatosensory cortex (S1). Rats learned to discriminate the location of IR sources in Ͻ4 d. Animals in which IR informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 58 publications
1
43
0
Order By: Relevance
“…Interestingly, when the directionality of the ICMS was reversed such that stimulation occurred when moving away from the platform (μ = 180°), rat Sa reached a performance plateau statistically indistinguishable from the visual cue baseline (t[46] = −0.96; P = 0.345). First, this result demonstrates reversal learning of our encoding paradigm, whereby after first learning one ICMS contingency, the animal had the capacity to remap the appropriate behavioral response to a new ICMS contingency (26). Second, it shows that even when ICMS encoded the platform direction with very low acuity, the rat learned to locate the platform with the same proficiency as with a visual cue.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…Interestingly, when the directionality of the ICMS was reversed such that stimulation occurred when moving away from the platform (μ = 180°), rat Sa reached a performance plateau statistically indistinguishable from the visual cue baseline (t[46] = −0.96; P = 0.345). First, this result demonstrates reversal learning of our encoding paradigm, whereby after first learning one ICMS contingency, the animal had the capacity to remap the appropriate behavioral response to a new ICMS contingency (26). Second, it shows that even when ICMS encoded the platform direction with very low acuity, the rat learned to locate the platform with the same proficiency as with a visual cue.…”
Section: Resultsmentioning
confidence: 71%
“…Prior work has shown that rats can learn to discriminate between 4 potential goal locations on the basis of ICMS delivered when their heading coincides with the direction of the true goal location (35). Several variations on this result were subsequently reported (26,36,37). Our sensory BMI experiment also used a searching task with goal direction feedback.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Building up a corresponding computational theory will deepen our understanding about the extensibility of the central nervous system and the organism-machine hybrid intelligence. It seems clear from experimental results that we have not come close to exhausting the potential for incorporating novel sources of information into cortical processing modes 14 , this also raises a very interesting question: can we know or prove that we can already perceive all the dimensions of the world?…”
Section: Discussionmentioning
confidence: 99%
“…However, a number of open questions remain, such as the optimal timescale or distribution of timescales for adaptation and whether the degree of adaptation must be matched to the properties of the specific neurons being stimulated. Work in primates 6,32 and rats 33 suggests that the plasticity of the brain will allow even a few channels of stimulation to become effective at providing a rich sensory experience, and complex spatiotemporal coding 34 with enough bandwidth to be clinically useful.…”
Section: Discussionmentioning
confidence: 99%